Attitude of progymnasiums students towards health and physical activeness - Mockevičienė, Daiva; Miliūnienė, Lina; Žukauskaitė, Renata; Dobrovolskytė, Ilona (Social Welfare: Interdisciplinary Approach, 2014)
The purpose of the study is to evaluate the attitude of 8 form students of Šiauliai city progymnasiums towards health and physical activeness. The study was attended by 870 (out of 1088) 8 form students of Šiauliai city progymnasiums. Questionnaire survey was chosen as the main research instrument. The research was conducted employing quantitative research methodology. The respondents of the research were given out questionnaires, the data of which were systematised, analysed and presented in graphs.